Knowledge of facts mediate "continuous improvement" in elite sport: a comment on Stanley and Krakauer (2013) - Toner, J. (Frontiers in Human Neuroscience, 2014)
Traditional theories of motor skill learning (e.g., Fitts and Posner, 1967) and many contemporary perspectives in sport psychology (see Masters and Maxwell, 2008) and cognitive neuroscience (see Yarrow et al., 2010) argue that skilled action is guided by procedural or implicit knowledge. Researchers adopting this perspective believe that skilled performance proceeds rapidly, efficiently and without the need for conscious monitoring, or a reliance on propositional knowledge (what some might term declarative or explicit knowledge) to guide an activity. However, in a recent paper published in this journal, Stanley and Krakauer (2013) present a compelling argument which offers a stern challenge to the latter of these assumptions. Drawing on evidence from famous cases in neuroscience (e.g., the case of HM) and other research on the nature of skill, Stanley and Krakauer (2013) suggest that becoming proficient at any motor task, and maintaining and improving one's skill in that activity, is heavily influenced by the use of what they refer to as "knowledge of facts" (i.e., propositional knowledge). The aim of this brief commentary is to build on Stanley and Krakauer's work by pointing to empirical evidence (e.g., Collins et al., 1999), recent theory (e.g., Shusterman, 2009) and phenomenological descriptions (e.g., Cotterill et al., 2010) which suggest that "continuous improvement" at the elite level of sport is mediated by the "ongoing accrual and improving application of knowledge of facts about an activity" (Stanley and Krakauer, 2013, p. 2). More specifically, the current paper presents evidence which demonstrates how performers use knowledge of facts in two distinct sporting situations: (1) in the training context when the performer is seeking to improve "attenuated" movement patterns and (2) during the planning and strategizing that occurs in pre-performance routines during on-line competitive performance.